"Plantations, privatization, poverty and power" - "Mayers, James (ed.)" (london, 2005)
Private sector delivery of state services is increasingly common worldwide, and state forest plantation management is no exception. Increasingly governments are transferring rights and responsibilities to the private sector for state-owned plantations. Some claim that this is the road to achieving sustainable forest management, greater contributions to local livelihoods and poverty reduction, others disagree. This book examines the evidence and explores the many issues raised by these changing relationships between the state, the private sector and local livelihoods. Experiences from around the world are described through seven case studies from Australia, China, Chile, India, New Zealand, South Africa and the United Kingdom, and key lessons and clear guidance are provided on how governments can best achieve a balance between private and public involvement while continuing to deliver the key social goods and services expected by all citizens.
Keywords: Forest resources-management